If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7+26m=42+19m
We move all terms to the left:
7+26m-(42+19m)=0
We add all the numbers together, and all the variables
26m-(19m+42)+7=0
We get rid of parentheses
26m-19m-42+7=0
We add all the numbers together, and all the variables
7m-35=0
We move all terms containing m to the left, all other terms to the right
7m=35
m=35/7
m=5
| 5y+14=7y+46 | | x-10=-15x-6 | | 3(4x+1)=3+12-5 | | 128÷8=o | | 4y+6=6y+24 | | y(y-31)=0 | | 3^x=3.5x | | m(m+23)=-132 | | ¾n-18=¼n-4 | | 7x-6x-3=8 | | -6=4-5x | | 12.89=2g+3.61 | | 51/5+13/10=x13 | | 7x+8-2=6-7x | | 3x-8=-1x | | F(x)=x(x)+6 | | 8x-7x-4=6 | | 10x-5=10x-2 | | -19+k=-38 | | 10x-5=4x+25 | | x5=1 | | 2x-12+4x=2-1x | | 51/5+13/1=13x | | -6+s=17 | | 7/8(z)=-2/9 | | 0.12x=120 | | |d|=-2 | | 11x-8x+10=3 | | 1/x+5-1/x+8=1/x+3-1/x+6 | | x2-3x=5x | | 8x-5+4x-7=180 | | 3.8x-(-1-9.7x)=2.613.3x |